DOES A PERINATAL PARENTING INTERVENTION WORK FOR FATHERS? A RANDOMIZED CONTROLLED TRIAL. Issue 6 (19th October 2018) - Mihelic, Mandy; Morawska, Alina; Filus, Ania
ABSTRACT: Fathers are increasingly expected to contribute to their parenting role at the transition to parenthood; however, many fathers experience mental health problems during this time. Parenting support for new fathers is limited, and research often only includes the mothers in intervention studies. Clear evidence for parenting programs for fathers has not yet been established. This study evaluated the effects of a parenting intervention (Baby Triple P) on fathers who were expecting their first baby. The design was a randomized controlled trial comparing Baby Triple P with care as usual over three time points (pregnancy, 10 weeks' postbirth, and 6 months' postbirth) for 112 fathers living in Brisbane, Australia. The primary outcomes included paternal psychological distress such as depression, anxiety, and stress and several secondary measures. No significant intervention effects for Baby Triple P were found at either post‐ or follow‐up assessments. Fathers in both groups reported significant increases in their parenting confidence and self‐efficacy. The results indicate no conclusive evidence for the effectiveness of Baby Triple P for new fathers. Future research using a sample with greater likelihood of experiencing problems at the transition to parenthood is needed as is offering more tailored need‐based support to obtain substantial evidence for this preventative parenting program.